STEM EDUCATION AS A TECHNOLOGY FOR DEVELOPING STUDENTS' CREATIVE ABILITIES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article about the STEAM training technology which unites the several branches of sciense. It means for developing skills such as critical thingking,cteativ thingking, researching skills , working in group, undestranding problems, application of scientific methodos, engineering approach, khowledges of bazic design. Projects on the STEAM approach are recommendet.